Efektivitas The Effectiveness of the Personal Data Protection Act (PDP Act) in Preventing Data Leaks in the Digital Era - Ghozi Ghozi (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
The digital era has facilitated the exchange of information, but at the same time, it has increased the threat of mass personal data leaks. In response, Law Number 27 of 2022 concerning Personal Data Protection (PDP Law) was enacted as the primary legal instrument in Indonesia to safeguard individuals' rights over their data and ensure the accountability of data managers. This study investigates the effectiveness of the PDP Law in preventing data leak incidents across various industries. Using qualitative methods including a literature review and case studies, this paper explores how data protection principles are applied, how law enforcement works, and the challenges faced in implementing the law. Although the PDP Law establishes a comprehensive legal structure, its impact remains limited by factors such as low public awareness, a lack of law enforcement resources, and rapid technological change. Therefore, ongoing collaboration between the government, businesses, and the public is crucial to improve compliance and ensure robust personal data protection in Indonesia.